1979
DOI: 10.4315/0362-028x-42.10.784
|View full text |Cite
|
Sign up to set email alerts
|

Toxin Production by Clostridium botulinum in Shelf-Stable Pasteurized Process Cheese Spreads

Abstract: Five non-refrigerated, pasteurized process cheese spreads, considered shelf-stable, were studied for their ability to support growth and toxin production by spores of Clostridium botulinum types A and B. Based on pH and water activity (aw) Cheese with Bacon, Limburger, Cheese Whiz, Old English, and Roka Blue cheese spreads were selected for the study. The pH ranged from 5.05 to 6.32 and the aw from 0.930 to 0.953. Fifty jars of each cheese spread were inoculated with 24,000 spores each; an additional 50 jars o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

1988
1988
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 4 publications
0
4
0
1
Order By: Relevance
“…and postpasteurization pathogenic bacteria such as Listeria monocytogenes , Salmonella spp., Staphylococcus aureus , and E. coli O157:H7 (Glass and Doyle 2005). Research has indicated that the most common microorganisms associated with process cheese are of the genus Clostridium (Kautter and others 1979; Sinha and Sinha 1988; Glass and Doyle 2005). A few outbreaks involving botulism from the consumption of canned PCS have been reported over the years (Glass and Doyle 2005).…”
Section: Microbiology Of Process Cheesementioning
confidence: 99%
“…and postpasteurization pathogenic bacteria such as Listeria monocytogenes , Salmonella spp., Staphylococcus aureus , and E. coli O157:H7 (Glass and Doyle 2005). Research has indicated that the most common microorganisms associated with process cheese are of the genus Clostridium (Kautter and others 1979; Sinha and Sinha 1988; Glass and Doyle 2005). A few outbreaks involving botulism from the consumption of canned PCS have been reported over the years (Glass and Doyle 2005).…”
Section: Microbiology Of Process Cheesementioning
confidence: 99%
“…The a, of these products ranges from 0.930 to 0.953 and the pH from 5.0 to 6.3 (Kautter et al, 1979). They have been consumed for many decades with no incidence of botulism attributed to them (Sperber, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…S., pasteurized process cheese spreads (e.g., cheese with bacon, Limburger, Cheez Whiz@, Old English@, Roka Blue'@) are traditional examples. The a, of these products ranges from 0.930 to 0.953 and the pH from 5.0 to 6.3 (Kautter et al, 1979). They have been consumed for many decades with no incidence of botulism attributed to them (Sperber, 1982).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Os Além destes dois fatores, pode-se citar também o efeito protetor contra esporulados que os polifosfatos conferem ao requeijão, fato enfatizado por diversos autores em trabalhos publicados sobre o assunto (BERGER et al, 1997b;BRIOZZO et al, 1983;ECKNER et al, 1994;KAUTTER et al, 1979;KAUTTER et al, 1981;TANAKA et al, 1986).…”
Section: Análises Microbiológicasunclassified